Etika Guru Dalam Proses Belajar Mengajar - Ruslan, Ruslan (Al-Riwayah : Jurnal Kependidikan, 2016)
The teacher is a figure of people who has a respectable and noble position. It is, as the phrase al-Ghazali, “the most glorious creature in the kingdom of heaven is a man who knows, practice and teaching. Teachers like the sun that illuminates him and others “. Thus, teachers are believed to occupy key positions in education. Teacher or educator is also ta figure which will give effect to the pupils or students. Therefore, a teacher must be someone who can guide and emulated as a role model in terms of both personal knowledge and behavior. The ideal teacher should have a certain number of qualifications related to the physical, ethical or moral or scientific. Ethical terms are also often used in three inter-related differences. The first is a general pattern or way of life. The second is set of rules or “moral code”, and the third is investigation about the way of life and rules of behavior.